Hypoalbuminemia as an Unusual Presentation of Undiagnosed Atypical Celiac Disease in an 84-Year-Old Woman - Filip Ernoić; Marko Vodanović; Ana Maria Vrga; Marinko Marušić; Filip Sedlić; Krešimir Luetić (Annals of Geriatric Medicine and Research, 2025)
Celiac disease is a chronic, immune-mediated enteropathy that is precipitated by dietary gluten in genetically predisposed individuals. Gastrointestinal symptoms and signs of malabsorption characterize a classical form of the disease, while patients with nonclassical celiac disease lack significant gastrointestinal symptoms. We report an uncommon case of celiac disease in an 84-year-old oligosymptomatic female with a recently treated colon tumor, diagnosed during the investigation of profound hypoproteinemia and hypoalbuminemia. In this case, two factors could have been misleading about the cause of hypoalbuminemia: malignant tumor and advanced age. Since the oncological disease was in remission, and the albumin concentration in the healthy elderly people in the community usually exceeds 38 g/L until after the age of 90, we pursued an alternative cause, leading to the diagnosis of celiac disease. Even in the absence of intestinal symptoms, advanced age, or other diagnoses, celiac disease should be considered a potential differential diagnosis in every patient presenting with hypoalbuminemia.